Performa Motor Bakar Satu Silinder 4-Tak Dengan Ground Strap Kabel Koil Sistem Pengapian (Variasi Panjang Kawat) - Eko Surjadi; Wijoyo Wijoyo; Arifin Arifin (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The research aims to examine the relationship and comparison of motor performance when using a ground strap cable for the secondary circuit of the ignition system, as well as to determine the length of the ground strap wire which results in better engine performance. The ground strap is in the form of a coil of cable outside the spark plug cable, whose function is to catch stray frequencies. With this tool, the electric current to the spark plug is claimed to be more focused, and the flame automatically becomes more stable and optimal. The research variables used to answer the above objectives are: independent variable, ground strap wire length, dependent variable power, torque and specific fuel consumption for a single cylinder 4-stroke motorbike and control variables, working temperature of the Honda Blade 110 cc motorbike and room temperature. The results of the research show that the performance produced for the four coil cable treatments, namely without and with the use of ground with different lengths, is increasingly decreasing, while specific fuel consumption shows that the higher the motor rotation, the lower the KBBS produced. The longer the ground strap wire, the better the motorbike performance. Without the use of a ground strap, motorbike performance is still better, 1,891 hp/4000 rpm, 3,366 Nm/4000 rpm and 0.139 kg/h/hp/4,000 rpm higher than using a ground strap with a wire length of 28 cm, namely 1,722 hp; 3,066 Nm and 0.166 kg/h/hp at 4000 rpm. The conclusions obtained are as follows: maximum motor performance is best for spark plug cables without using a ground strap but is unstable with each increase in rotation, while for coil cables with a ground strap the maximum performance sequentially increases with variations in the length of the copper wire winding in the coil cable. Power and torque decreased by 11%, while fuel consumption increased by 13% compared to without the use of a ground strap.